PERMAINAN SCRABBLE MODIFIKASI TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK TUNAGRAHITA RINGAN DI SLB C - Sunnaturrizkiya, (Jurnal Pendidikan Khusus, 2016)
Abstract The mentally retardation children had obstacle in speech i.e. reading ability. This happened because of less interesting learning, less motivating children, and monotone tendency. Therefore, it required learning suitable with the characteristics of mentally retarded children by playing scrabble modification. Playing scrabble modification was playing activity which gave priority to form words and the activity of reading alphabets, syllables, words, and sentences. Playing scrabble modification was also interesting and modern playing activity. The purpose of this research was to prove the influence of scrabble modification game toward beginning reading ability to mild mentally retardation children in SLB Al-Chusnaini Sukodono. This research used quantitative approach with pre-experimental kind and Wilcoxon Match Pairs Test. The sample in this research was all the second class mentally retardation children in SLB Al-Chusnaini Sukodono whose ability of beginning reading was low. The total sample in this research was seven children. The technique of data collection used the result of observation and documentation. The research result indicated that the beginning reading ability of mild mentally retardation children in SLB Al-Chusnaini Sukodono before giving scrabble modification game was averagely obtained 41,07 and the beginning reading ability of mild mentally retardation children in SLB Al-Chusnaini Sukodono after giving scrabble modification game was averagely obtained 71,42. In addition, the research result also indicated T counted = 0 was smaller than T table = 2 with the significant level 5%. If T counted < T table (0<2), so it could be concluded that there was influence of scrabble modification game toward the beginning reading ability of mild mentally retardation children in SLB Al-Chusnaini Sukodono.   Key words:  scrabble modification, beginning reading